International Survey on the Use of Emerging Technologies Among Forensic and Correctional Mental Health Professionals. (February 2023) - Kirschstein, Madeleine A.; Singh, Jay P.; Rossegger, Astrid; Endrass, Jérôme; Graf, Marc
Although the global diffusion of e-mental health has increased in recent years, research on the use of technologies in criminal justice settings is limited. To bridge this knowledge gap, we conducted an international online survey ( N = 555) of forensic and correctional mental health professionals from Germany, Switzerland, the United Kingdom, the United States, and 20 additional countries. Telecommunication technologies and mental health platforms had the highest numbers of users, the broadest scope, and the largest increase in use due to the coronavirus disease 2019 (COVID-19) pandemic. In contrast, the use of social media and advanced technologies was lower, narrower in scope, and remained the same or decreased during the COVID-19 pandemic. Respondents' age, professional discipline, country, and clinical setting significantly predicted total technology use in clinical practice. The study findings provide an overview of the current patterns of technology use and point to opportunities for research and development.